Augmented reality as an interactive media solution in clay craft learning in junior high school - Risandi, Rizki; Martono, Martono (Universitas Negeri Yogyakarta, 2024)
This research aims to describe the development, use, and feasibility of augmented reality clay learning media for craft learning in junior high school. This research is a research and development (R&D) using the 4D model, namely define, design, development and dissemination. The resulting product is augmented reality-based learning media of clay craft material. The feasibility of the media is assessed using a media and material expert validation questionnaire. The results of this study indicate that augmented reality clay learning media has been successfully developed to increase interest in learning and mastery of soft craft materials. Augmented reality students can use clay learning media, which can increase student interest in learning. Clay augmented reality learning media is feasible to use in junior high school and is able to increase students' interest in learning. This is evidenced by the results of usability testing stating that augmented reality clay learning media can be learned, efficient, easy to remember, safe to use, and provide a level of satisfaction for students. This augmented reality clay media is feasible to be used as a learning medium in junior high school.